A three-dimensional analysis of drying of a single suspension droplet in high rate evaporation processes. (August 2020) - Javid, Seyyed Morteza; Moreau, Christian; Mostaghimi, Javad
Highlights: Three-dimensional modeling of successive states drying of a single suspension droplet in high rate evaporation processes. Finding a criterion for onset of buckling of evaporating suspension droplet. Investigation of effect of physical properties on the buckling and consequently deformation of the suspension droplet Abstract: A three-dimensional model based on Fast Interface Particle Interaction (FIPI) is developed for drying a single suspension droplet in processes with a high evaporation rate. The numerical model is able to describe consecutive states of the agglomeration process, including droplet shrinkage, particle accumulation on droplet surface, and buckling. Also, the three-dimensional analysis sheds more light on the complex phenomena of buckling, especially the interaction of the droplet interface and suspended solid particles. The model uses a Lagrangian approach for tracking suspended solid particles and the Eulerian approach for the liquid phase. It is found that particle-induced surface pressure drives the buckling of the suspension droplet. It is shown that the particle-induced surface pressure reaches a threshold value at the onset of buckling. In addition, the model allows us to further investigate the effect of physical properties like the ratio of solid particle size to suspension droplet size, liquid surface tension, and rate of evaporation on the buckling and consequently deformation of the suspension droplet.